2021
DOI: 10.3389/fphar.2020.608199
|View full text |Cite
|
Sign up to set email alerts
|

Dichondra repens J.R.Forst. and G.Forst.: A Review of Its Traditional Uses, Chemistry, Pharmacology, Toxicology and Applications

Abstract: Ethnopharmacology relevance:Dichondra repens J.R.Forst. and G.Forst (DRF; Convolvulaceae, called Matijin in Chinese), has been traditionally used to treat jaundice, bacillary dysentery, urinary tract infection, edema, contusions, and strains and sprains based on traditional Chinese medicine (TCM) concepts.Aim of study: This paper intends to provide a comprehensive and critical analysis of research on DRF focusing on a relationship between traditional uses and pharmacological effects, evaluating the therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Matijin-Su [N-(N-benzoyl-L-phenylalanyl)-O-acetyl-L-phenylalanol, MTS] is a phenylalanine dipeptide monomer compound with various biological activities, and it was originally isolated from a Chinese ethnic medicine Matijin (Dichondra repens Forst.) [11,12]. MTS derivatives display various pharmacological activities, including anti-hepatitis B virus (HBV) [13][14][15], hepatoprotective activities [11,16], anti-inflammatory activities [11], and a promising anti-tumor ability [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matijin-Su [N-(N-benzoyl-L-phenylalanyl)-O-acetyl-L-phenylalanol, MTS] is a phenylalanine dipeptide monomer compound with various biological activities, and it was originally isolated from a Chinese ethnic medicine Matijin (Dichondra repens Forst.) [11,12]. MTS derivatives display various pharmacological activities, including anti-hepatitis B virus (HBV) [13][14][15], hepatoprotective activities [11,16], anti-inflammatory activities [11], and a promising anti-tumor ability [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…[11,12]. MTS derivatives display various pharmacological activities, including anti-hepatitis B virus (HBV) [13][14][15], hepatoprotective activities [11,16], anti-inflammatory activities [11], and a promising anti-tumor ability [17,18]. Studies have shown that MTS derivatives 13b, 13c, and 14a showed a significantly higher inhibitory activity on HBV DNA replication than the positive control lamivudine did [19].…”
Section: Introductionmentioning
confidence: 99%